1. Рассмотрим выражение: \[ \left(0-\frac{1}{2}\right)^2 + \left(-3 + 6\right)^3 - \left(1.2^{4} - 10\right)^2 \].
Решим поэтапно:
- \( \left(0-\frac{1}{2}\right)^2 = \left(-\frac{1}{2}\right)^2 = \frac{1}{4} \).
- \( \left(-3 + 6\right)^3 = 3^3 = 27 \).
- \( 1.2^4 = 1.2 \cdot 1.2 \cdot 1.2 \cdot 1.2 = 2.0736 \), следовательно \( 1.2^4 - 10 = -7.9264 \), тогда \( \left(-7.9264\right)^2 = 62.8348 \).
- Подставляем: \( \frac{1}{4} + 27 - 62.8348 = 27.25 - 62.8348 = -35.5848 \).
Итак, \( \boxed{-35.5848} \).